The Nature and Persistence of Buyback Anomalies - Peyer, Urs; Vermaelen, Theo (Review of Financial Studies, 2009)
[Using recent data, we reject the hypothesis that the buyback anomalies first reported by Lakonishok and Vermaelen (1990, Journal of Finance 45:455-77) and Ikenberry, Lakonishok, and Vermaelen (1995, Journal of Financial Economics 39:181-208) have disappeared over time. We find evidence consistent with the hypothesis that open market repurchases are a response to a market overreaction to bad news: significant analyst downgrades, combined with overly pessimistic forecasts of long-term earnings. Stock prices after tender offers are set as if all investors tender their shares, but empirically they do not. Thus, the arbitrage opportunity persists because the market sets prices as if the average, not the marginal investor, determines the stock price]